Insulin Therapy in Diabetic Hyperglycemic Emergencies - Diana Machado Ramírez; Manuel Licea Puig (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Background: diabetic ketoacidosis and hyperglycemic hyperosmolar nonketotic state are two of the most serious metabolic emergencies in diabetic patients. Objective: to identify the type of metabolic complications (diabetic ketoacidosis and hyperglycemic hyperosmolar nonketotic state) in order to analyze the patients' outcome considering the plasma pH levels, as well as the mode of insulin administration. Method: a cross-sectional descriptive study was conducted in 52 patients admitted to the intensive care unit of the Enrique Cabrera Hospital from 2000 to 2007. The variables analyzed included: type of diabetes mellitus, type of acute complication, mode of insulin administration, blood gas analysis and outcome. Results: diabetic ketoacidosis occurred in 57.5 % of the type 1 diabetic patients and in the 42.5 % of the type 2 diabetics. None of the type 1 diabetics developed hyperglycemic hyperosmolar nonketotic state and this complication was observed in 23.0 % of the patients with diabetes type 2. Microdosing was the mode of insulin administration that predominated in both ketoacidosis and hyperglycemic state cases. Mortality was higher in the hyperglycemic state (67 %) and using microdoses in the insulin therapy. Conclusions: diabetic ketoacidosis was the major complication. Mortality from diabetic ketoacidosis and hyperglycemic hyperosmolar nonketotic state was high and the mode of insulin administration was inadequate in some patients.